2018
DOI: 10.20964/2018.09.21
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Manganese oxide Films for High performance Supercapacitors

Abstract: Nanostructured manganese oxide films, including continuous coating, nanoflower film and nanowall array, were electrodeposited on nickel foils via anodic electrodeposition. The as-prepared samples were tested as electrodes for supercapacitors and excellent capacitive performances were achieved. Among them, the nanowall array, which was composed of interconnected ultrathin nanosheets, exhibited the highest specific capacitance of 327 F g-1 at 1 A g-1. The specific capacitance could retain as high as 317 F g-1 af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The pores may be formed during the freezing process after removing the water and the like . The 3D porous structure composed of thin and curved nanosheets favors the sufficient contact of the electrode with the liquid electrolyte, which is helpful to shorten the zinc ions’ diffusion distances during the charge or discharge processes. TEM images (Figure c,d), including high-resolution TEM (HR-TEM) images, further reveal the ultrathin property of the building block nanosheets (∼several atomic layers’ thickness). It is found in the HR-TEM image (Figure d) that the interplanar spacing is ca.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The pores may be formed during the freezing process after removing the water and the like . The 3D porous structure composed of thin and curved nanosheets favors the sufficient contact of the electrode with the liquid electrolyte, which is helpful to shorten the zinc ions’ diffusion distances during the charge or discharge processes. TEM images (Figure c,d), including high-resolution TEM (HR-TEM) images, further reveal the ultrathin property of the building block nanosheets (∼several atomic layers’ thickness). It is found in the HR-TEM image (Figure d) that the interplanar spacing is ca.…”
Section: Resultsmentioning
confidence: 98%
“…In spite of the intrinsic crystal structure, external micromorphologies could also affect greatly the rate performance of the host materials. It is found that a two-dimensional (2D) structure favors to alleviate effectively the diffusion distance of charged ions and electrons during charge or discharge processes, which is helpful to enhance the rate performance. Besides, electrical conductivity could influence the cathode performance notably as well, which could be enhanced by coating or decorating with conductive materials, such as carbon or silver. It is favorable and desirable to fabricate the 2D vanadium-based oxide nanosheets coated with carbon as a cathode host for fast and stable zinc storage.…”
Section: Introductionmentioning
confidence: 99%
“…Several label‐free techniques have been developed for whole cell sensing, including optical waveguide spectroscopy, resonant waveguide grating, reflectrometric interference spectroscopy, surface plasmon resonance (SPR), and non‐optical methods such as impedance spectroscopy and quartz crystal microbalance . The use of many of these techniques for whole cell sensing has recently been reviewed in the literature . However, most of these methodologies have been applied to monitor cell– or bacteria–surface interactions, morphological changes in cells caused by environmental changes, monitoring cell interactions, and cell responses with drugs, small molecules, and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…A three-electrode system comprising of a saturated calomel electrode (SCE) electrode (as the reference electrode), a platinum sheet (as the auxiliary electrode), and the samples (as the working electrode) was applied for the electrochemical tests. [10][11][12] The corrosion behavior of the samples was characterized by potentiodynamic polarization on a CHI660E electrochemical workstation. Before each potentiodynamic test, the samples were first stabilized at open-circuit potential (OCP) for 5 min, then started potential sweep from À0.2 V (vs. OCP) to 2.0 V (vs. SCE) with a scanning rate of 10 mV s À1 .…”
Section: Electrochemical Testsmentioning
confidence: 99%